Alzheimer's protection effect of A673T mutation may be driven by lower Aβ oligomer binding affinity. Issue 4 (25th October 2020) - Limegrover, Colleen S.; LeVine, Harry; Izzo, Nicholas J.; Yurko, Raymond; Mozzoni, Kelsie; Rehak, Courtney; Sadlek, Kelsey; Safferstein, Hank; Catalano, Susan M.
Abstract: Several mutations conferring protection against Alzheimer's disease (AD) have been described, none as profound as the A673T mutation, where carriers are four times less likely to get AD compared to noncarriers. This mutation results in reduced amyloid beta (Aβ) protein production in vitro and lower lifetime Aβ concentration in carriers. Better understanding of the protective mechanisms of the mutation may provide important insights into AD pathophysiology and identify productive therapeutic intervention strategies for disease modification. Aβ(1‐42) protein forms oligomers that bind saturably to a single receptor site on neuronal synapses, initiating the downstream toxicities observed in AD. Decreased formation, toxicity, or stability of soluble Aβ oligomers, or reduction of synaptic binding of these oligomers, may combine with overall lower Aβ concentration to underlie A673T's disease protecting mechanism. To investigate these possibilities, we compared the formation rate of soluble oligomers made from Icelandic A673T mutant and wild type (wt) Aβ(1‐42) synthetic protein, the amount and intensity of oligomer bound to mature primary rat hippocampal/cortical neuronal synapses, and the potency of bound oligomers to impact trafficking rate in neurons in vitro using a physiologically relevant oligomer preparation method. At equal protein concentrations, mutant protein forms approximately 50% or fewer oligomers of high molecular weight (>50 kDa) compared to wt protein. Mutant oligomers are twice as potent at altering the cellular vesicle trafficking rate as wt at equivalent concentrations, however, mutant oligomers have a >4‐fold lower binding affinity to synaptic receptors ( K d  = 1, 950 vs. 442 nM). The net effect of these differences is a lower overall toxicity at a given concentration. This study demonstrates for the first time that mutant A673T Aβ oligomers prepared with this method have fundamentally different assembly characteristics and biological impact from wt protein and indicates that its disease protecting mechanism may result primarily from the mutant protein's much lower binding affinity to synaptic receptors. This suggests that therapeutics that effectively reduce oligomer binding to synapses in the brain may be beneficial in AD. Abstract : Carriers of the A673T mutation are four times less likely to get Alzheimer's disease than noncarriers. We showed that mutant amyloid beta (Aβ) oligomers bind less, and with lower affinity as well as intensity, to synaptic puncta than wt Aβ oligomers. This study demonstrates for the first time that mutant A673T Aβ oligomers have fundamentally different assembly characteristics and biological impact from wt peptide, and indicates that its disease protecting mechanism may result primarily from the mutant peptide's much lower binding affinity to synaptic receptors.